An annotated bibliography of Ibanag culture and history a preliminary survey - Canapi, Aurora C.; Arsenio, Manuel E. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1975)
There are 288 annotated entries in this bibliography gathered from different collections and bibliographic aids and indexes at the U.P. Library, the De la Salle Library, Lopez Memorial Museum, the National Library, National Teachers' College Library, Univeristy of Santo Tomas Library, and Ateneo de Manila University Library. The materials so gathered cover matters relating to the customs, economic, educational, social, political and recreational life of the Ibanags, their supersitutious beliefs in the early times and later their conversion to christianity by the early Dominican Fathers during the Spanish period, the early exploration of the region by the Spaniards, the wealth of fauna and flora of the region and the strong determination and energy of the Ibanags in bringing about rapid progress of their province.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Ibanag--Bibliography.; Ibanag--Social life and customs--Bibliography.